1991
DOI: 10.3109/03008209109152432
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K-Dependent Carboxylation in Articular Chondrocytes

Abstract: A nonhepatic vitamin K-dependent protein, matrix Gla protein, has recently been identified in cartilage where it may play an important role in the control of mineralization or matrix development. We have investigated the vitamin K cycle in chondrocytes isolated from bovine and rabbit articular cartilage and examined these cells for their ability to synthesize vitamin K-dependent proteins. Chondrocytes were found to have an active vitamin K-dependent carboxylation system. Preincubation of the cells with warfari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Abnormal articular-cartilage calcification has been seen in conditions such as chondrocalcinosis, hydroxyapatite deposition and osteoarthritis [8][9][10] and could be due to a local defect in MGP production. Recently we have discovered that articular-cartilage chondrocytes contain the necessary enzymes for the synthesis of vitamin K-dependent proteins and that they do synthesize MGP [11]. Our present studies demonstrate for the first time the presence and localization of MGP in bovine, monkey and human articular cartilage.…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…Abnormal articular-cartilage calcification has been seen in conditions such as chondrocalcinosis, hydroxyapatite deposition and osteoarthritis [8][9][10] and could be due to a local defect in MGP production. Recently we have discovered that articular-cartilage chondrocytes contain the necessary enzymes for the synthesis of vitamin K-dependent proteins and that they do synthesize MGP [11]. Our present studies demonstrate for the first time the presence and localization of MGP in bovine, monkey and human articular cartilage.…”
Section: Introductionsupporting
confidence: 65%
“…MGP appears to represent about 0.05 % of the total amount of cartilage protein extracted with guanidinium chloride, and the concentration of 0.5 jig/mg of tissue protein is consistent with concentrations noted in rat cartilages [2]. It has been shown that articularcartilage chondrocytes are capable of synthesizing a family of vitamin K-dependent proteins including MGP [11]. MGP is the first of this family to be isolated and characterized.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…g-Carboxylase activity g-Carboxylase activity was assayed in 24 h cultured chondrocytes from normal (n ¼ 2) and osteoarthritic tissues (n ¼ 2) as 14 CO 2 incorporation into the synthetic g-carboxylase peptide substrate FLEEL as described 9 . The reaction was triggered by adding chemically reduced vitamin K 1 H 2 (100 mg/ml) to the assay mixture.…”
Section: Partial Purification Of Human Bone Mgpmentioning
confidence: 99%
“…This modification of coagulation factors made in the liver is essential for normal hemostasis. We have shown previously that chondrocytes synthesize MGP and possess an active post-translational g-carboxylation system 9,10 .…”
Section: Introductionmentioning
confidence: 98%